On-line identification of current and position stiffnesses by lms algorithm in active magnetic bearing system equipped with force transducers - Kim, SJ; Lee, CW (ACADEMIC PRESS LTD, 1999)
For on-line identification of the current and position stiffnesses in an active magnetic bearing (AMB) system equipped with four pairs of built-in radial magnetic force transducers, a modified least-mean-squares (LMS) algorithm is proposed. The algorithm, which is based on a simple linearised magnetic force equation, utilises three kinds of measured signals, i.e. rotor displacement, control current and magnetic force. The simulation and Experimental results show that the proposed algorithm is very simple and effective in adaptively identifying the current and position stiffnesses of the AMB. (C) 1999 Academic Press.